Mongol ba Tüvd XX zuuny ėhnij hagast XIII Dalaj Lam Tüvdėnžamc Mongold zalarsan tüüh = Mongolia and Tibet in the beginning of the XXth century : XIIIth Dalai Lama Tubten Gyatso in Mongolia in 1904-1906 - Batbajar, C. 1957-; Gombosürėn, Dėndėvsürėngijn 1937- (Bembi San, 2009)
History of relationship between Mongolia and Tibet and visit of the 13th Dalai lama to Mongolia in 1904-1906